Transformation of Learning Management: Integrative Study of Islamic Boarding School Curriculum - Ilyasin, Mukhamad (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The existence of Islamic education e.g. Islamic boarding schools has contributed in in the middle of social lives in Indonesia. Continuously, Islamic boarding schools have developed in accordance with social demand nowadays. Besides, Islamic boarding school education should make adaptation by doing many changes especially in the field of learning management through curriculum integration of Salafiyah and Kholafiyah in order to build Islamic boarding school as central for excellent. Therefore, as an effort to achieve intended goal, observation and interview were conducted to obtain the data regarding with description of learning management especially concerning with Salafiyah and Kholafiyah curriculums at Nabil Husein Islamic boarding school Samarinda. The findings indicate that the value of Islamic boarding school is assumed as a core value of curriculum development as shifting paradigm through Islamic boarding school learning management. That paradigm has correlation with institutional goals of Nabil Husein i.e. as Islamic education main controller with religious and moral values oriented. In addition, graduates of Nabil Husein are expected to master two types of knowledge fields i.e. general and Islamic knowledges with spiritual values, so that Islamic boarding school education graduates are able to integrate among social, emotion, and intelligence quotients. Further implication is also noticed and suggested in this research.